Statistical Approach to the Analysis of Corporate Culture Interaction Process - Matraeva, Liliia V.; Konov, Alexey A.; Belyak, Alexey V. (International Review of Management and Marketing, 2016)
The study develops a method that enables to perform quantitative comparison of corporate cultures, mathematically assess the effectiveness of cross-cultural interaction and identify sources of potential conflicts. Research is based on the criteria of corporate culture differentiation developed by Geert Hofstede. Study applies traditional methods of statistic analysis, such as decile method, maxmin method and Gini coefficient in order to examine the differentiation of each criterion separately. Further on, multicriterial statistic methods are used to create graphic imprint of national corporate culture. Finally the two imprints are overlapped, which allows to identify sources of conflicts and measure overall effectiveness of cross-cultural interaction. The paper reflects a quantitative instrument that allows to measure cross-cultural conflictness and identify, which of the four criteria influences it the most. The method can be applied at any level, from measuring conflictness between two departments of a company to assessing ROI of transnational companies coming to new markets. The study provides valuable information regarding the interaction of corporate cultures and enables to address this traditionally empiric question from statistical point of view. Keywords: Cross-cultural interaction, corporate culture, differential analysis, interaction efficiency, cultural criteria, social analysis JEL Classifications: C15; M14; M54